An investigation of agile manufacturing enablers in Indian automotive SMEs using structural equation model. Issue 3 (5th September 2018) - Goswami, Mohit; Kumar, Gopal
Abstract : Purpose: This paper aims to analyze the agile manufacturing practices in small and medium enterprises (SMEs) within the auto-ancillary sector spread across eastern India. Using statistical method, a number of crucial insights have been captured and discussed in detail. Design/methodology/approach: A structural equation model (SEM) encapsulating pertinent agile manufacturing attributes and enablers as the focal construct is conceptualized and validated in this research. The SEM model is evolved in a manner that agile attributes and agile enablers are modeled as latent dependent and manifest variable, respectively. Findings: A number of key hypothesis entailing interactions of key agility enablers, i.e. manufacturing responsiveness agility, manufacturing strategy agility, workforce agility, technology agility, manufacturing management agility, etc. are conceptualized and validated. Originality/value: The authors specifically focus on evolving agile manufacturing framework (characterized by agility enablers and attributes) that lies at the intersection of SMEs, automotive sector and an emerging economy.